Implementation Of The Triple Bottom Line In Cooperative Performance Assessment - JUNIARIANI, Ni Made Rai; LESTARI, Ni Luh Putu Ratna Wahyu (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study explores and describes the facts about what is felt and experienced directly by the informants in-depth on the application of the Triple Bottom Line (TBL) concept in cooperatives. The research uses a non-positivistic method with a qualitative design and a case study approach. Data analysis was carried out by conducting interviews with informants who were directly related to the implementation of the TBL concept, namely the chairman of the cooperative, the members of the cooperative, and the employees of the cooperative. Based on data analysis and in-depth interviews with informants, it can be concluded that the Savings and Loans Cooperative (KSP) Jumari has implemented the TBL concept well and the impact of this application for KSP Jumari is that the KSP Jumari economy always grows positively. This is inseparable from the active participation of members and employees of KSP Jumari themselves. This is inseparable from the trust of members to KSP Jumari and this is also the impact of the cooperative's concern for the environment so that the existence of KSP Jumari is better known. The financial condition alone is not enough to guarantee the value of the company to grow sustainably.